Socioeconomic status and remaining teeth in Japan: results from the Toyama dementia survey - Nobue Nakahori; Michikazu Sekine; Masaaki Yamada; Takashi Tatsuse; Hideki Kido; Michio Suzuki (BMC, 2019)
Abstract Background The prevalence of periodontal disease is increasing among elderly individuals in Japan. Reports on the risk factors for tooth loss have included socioeconomic status (SES); however, few studies have addressed the association between remaining teeth and SES by examining whether education and occupation have a synergistic effect on tooth loss. Accordingly, the present study evaluated the association of remaining teeth with the socioeconomic factors of educational and occupational histories in Japanese elderly individuals. Methods This retrospective case-control study used data from the Toyama Dementia Survey, Japan. Toyama Prefecture residents aged ≥65 years were randomly selected for the study (sampling rate, 0.5%), and 1303 residents agreed to participate (response rate, 84.8%). Structured interviews with participants and family members (or proxies, if necessary) were conducted. Participants' lifestyle factors (e.g., smoking and alcohol consumption), medical history, and SES (educational and occupational history) as well as the presence or absence of remaining teeth were assessed. The association between SES and remaining teeth was examined using a logistic regression analysis. Results Overall, 275 cases with no remaining teeth and 898 controls with remaining teeth were identified. The odds ratio (OR) for complete tooth loss was higher among less educated participants (≤6 years) than among highly educated participants [age- and sex-adjusted OR, 3.29; 95% confidence interval (CI), 1.90-5.71]; furthermore, it was higher among participants with a blue-collar occupational history than among those with a white-collar occupational history (age- and sex-adjusted OR, 2.16; 95% CI, 1.52-3.06). After adjusting for employment history or educational attainment, the ORs for tooth loss were 2.79-3.07 among less educated participants and 1.89-1.93 among participants with a blue-collar occupational history. A current or former smoking habit and medical history of diabetes and osteoporosis increased the risk of tooth loss. The interaction term of a low level of education and a history of blue-collar occupation with tooth loss was not significant. Conclusions In Japan, a low SES is a risk factor for tooth loss. A low level of education is a more important predictor of tooth loss than a blue-collar occupation.